Improving achievements of pupils with learning and behavior problems with co-operative teaching strategy in Aboh, Delta State, Nigeria - Ngozi Obiyo (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2011)
The purpose of the study was to determine the effects of cooperative teaching on children with learning and behavioral problems. Determining the most effective intervention for children with learning and behavioral problems has continued to challenge educators. For this the study sought to find out how co-operative teaching will improve the achievements of pupils with learning and behavior problems in Aboh, Delta State, Nigeria.  A research question and a hypothesis tested at 0.05 level of significance was used to guide the study. The research design was true experimental. Two groups of children were used for the study .The sample consisted of 64 primaries four and five pupils .From the study, it was found out that Experimental Group had higher mean of 76.06 against Control Group with mean of 53.84 and standard deviation of 19.2. The hypothesis was tested using t-test and showed that the performance of the experimental group was significantly higher than that of the control group. It is therefore recommended that this strategy should be included in the school curriculum for children with learning and behavior problems.